Faculty acceptance of blended learning in private Universities in China - Xianjun Dai; Nur Suhaidah Sukor; Noraini Said; He Sun (Human Resource Management Academic Research Society, 2024)
With the continuous development of educational informatization, blended learning, which takes into account both offline and online teaching, has attracted more and more attention. The faculty acceptance of blended learning directly influences the implementation and development of blended learning. This study aimed to examine the factors affecting behavioral intention to use blended learning based on UTAUT model among faculty in private universities in China. This study used a quantitative survey research design involving 138 private university faculty. The data was collected by an online survey and analyzed by descriptive statistics and inferential statistics. Results of this research revealed that performance expectancy and facilitating conditions have a significant effect on the behavioral intention to use blended learning. Additionally, the model accounted for 65.4% of the variance in acceptance of blended learning, indicating a substantial effect size. The practical implications inform policymakers and educational institutions on how to improve faculty acceptance of blended learning, therefore improving the implementation of blended learning.